Biblical Bestiary: Cattle (The Biblical archaeology review, 2021)
Across the ancient Near East, domesticated taurine cattle (Bos taurus) were valued sources of agricultural labor and sustenance. Essential in the so-called Neolithic revolution, which saw the transition of human society from nomadic hunter-gatherers to sedentary farming communities, cattle were first domesticated in the Fertile Crescent more than 10,000 years ago. Beef was consumed […]